Making Employment Services and Active Measures Sensitive to the Needs of Young People : Recommendations for Youth Employment Programs in Kosovo - Hempel, Kevin (World Bank, Washington, DC, 2020)
Young people are particularly disadvantaged in Kosovo’s labor market, facing high unemployment and precarious working conditions. In response, promoting youth employment has become a policy priority for the Government of Kosovo. Supporting young people’s employment prospects must consider that young people are different than adults. First, they face age-specific barriers in the labor market, such as lack of work experience and limited professional networks. Second, the youth years are a time of transition where young people build autonomy and identity and are strongly influenced by their social environment. These realities need to be considered for program design and implementation. Youth employment policies and interventions should therefore be sensitive to the specific needs and preferences of young people.